2008
DOI: 10.1063/1.2988262
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of defects upon annealing in He-implanted 4H-SiC

Abstract: The strain induced by room temperature helium implantation into 4H-SiC below the threshold amorphization dose results from both point and He-related defects. When the helium concentration is lower than 0.5% the strain profile follows the point defect profile, whereas at higher concentrations the He ions have a dominant effect on the strain. Upon annealing, the near surface strain progressively relaxes up to 1500 °C while the maximum strain relaxation stops at a temperature where helium ions agglomerate into pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 15 publications
7
41
4
Order By: Relevance
“…The profiles are normalized to the maximum elastic strain. Usually, it is found that the strain depth profile overlaps on one of the three above mentioned profiles [19][20][21]. Hence, as a starting point, the experimental damage profile (f D ), which is here found identical to the Cs distribution, and the theoretical nuclear energy loss profile (dE/dx) nucl , were taken as possible strain profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The profiles are normalized to the maximum elastic strain. Usually, it is found that the strain depth profile overlaps on one of the three above mentioned profiles [19][20][21]. Hence, as a starting point, the experimental damage profile (f D ), which is here found identical to the Cs distribution, and the theoretical nuclear energy loss profile (dE/dx) nucl , were taken as possible strain profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Ion irradiation can induce a great amount of structural damage in crystalline materials, including point defect, defect cluster, dislocation and amorphization zones [1][2][3]. Irradiation-induced phase transformation and structural modification have been reported in many previous studies [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 94%
“…Decrease of LS density from N(E F )=2. 4 [10]. The impact of  p on transport charge for values N(E F ) and   in band 1 is higher than in band 2 (figure4).…”
Section: Resultsmentioning
confidence: 99%
“…The study of the effect on the properties of RD in the ceramic SiC is difficult and leads to ambiguous results owing to its complex structural hierarchy and high content of impurities and biographical defects (BD). Improvement of electrical characteristics of the epitaxial layers of SiC in devices is achieved by the ion implantation and subsequent thermal annealing owing to an annihilation and redistribution of RD and modify of the structure of the material surface [4][5][6][7]. High-intensity short-pulse implantation (HISPI) of ions followed by heating of the surface layer provides simultaneous annealing of RD [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation